Análise da formação do profissional de administração a partir de dissertações e teses produzidas em Programas de Pós-Graduação em Educação - Gomes, Daniel Fernando Matheus (Universidade Federal de São Carlos, 2015)
The research deals with the formation of the Management professional, through the analysis of thesis and dissertations produced in graduate programs in Education. Is constituted as bibliographic research, having been developed in three stages: collection of bibliographic material; analysis of selected studies; integrating synthesis of the results. Defend that the role of Business Administration courses is to provide a critical view of reality, which means, in this case, does not offer a limited training to the demands of the labor market. To that end, structured work around the following research question: "what studies of the course of Directors produced under the Graduate Program in Education between the years 2004-2013 show on vocational training at the undergraduate level administrator?" Such a question has served as reference for the preparation of the overall objective: to analyze dissertations and thesis produced in Education on administrator training in order to provide information to think again that training in the Brazilian higher education. The overall objective was deployed in the following specific: raise Administration course trajectory in Brazil; analyze dissertations and theses on the design of them contemplated curriculum; analyze dissertations and theses about the Administration 's views on them defended and criticized ; analyze dissertations and theses about the labor market of ideas and the world of work present in them . The research corpus was composed of twenty- five papers coming from the graduate in Education in Brazil from 2004 to 2013. The programs theoretical framework is guided primarily in the Gimeno Sacristán's ideas on the process view of the curriculum; the critical analysis of management concepts found throughout its history; and the concepts of training for the labor market and the world of work. The main results presented in dissertations and theses analyzed in this research indicate that regarding the curriculum, the meeting addressed partial aspects, considering the design of Gimeno Sacristán, and the majority had as focus of analysis the curricular text, represented by the Project pedagogical Course , and few have analyzed the curriculum lived, or at work; on the design of Directors present in the works, almost all of them found lined courses in the capital 's perspective, involving a type of training geared to the labor market, although the authors of dissertations and thesis have advocated other that considers the interests of whole of society and be guided by the critical insertion of graduates into the labor market, consistent with the view taken in this research.
Analysis of the formation of tManagement professional from thesis and dissertations produced in the Graduate Program in Education.
Keywords: Currículo; Formação de administradores; Ensino superior; Training Management; Curriculum; Higher Education; CIENCIAS HUMANAS::EDUCACAO::CURRICULO